Study of the effect of a new polymeric anticorrosion coating in transporttechnological machines on noise and vibration - Botir D. Ibragimov; Nurillo T. Ergashev; Shotemur B. Shoikromov (Global Scientific Publishing, 2022)
The article explores the issues of increasing the durability of components and parts of the car body with polymeric anti-corrosion materials. Cars are constantly exposed to corrosion processes, and the durability of metal parts depends on the intensity of corrosion. This indicates the need for research and the importance of scientific and technical work in this area. Under laboratory conditions, on the basis of local raw materials, an anti-corrosion coating was synthesized - epoxy polyurethane with an additive. Corrosion protection was determined by the method of weight loss of metal plates in various aggressive environments, adhesion and corrosion protection, as well as the influence of noise and vibration. Field tests were carried out on MAN CLA 26.280 after its preliminary preparation.
Keywords: polymer protective coatings; anti-corrosion coating; epoxy resin; noise